The influence of Alasdair MacIntyre's After Virtue book on business ethics studies: A citation concept analysis - Akgun, Ali E.; Keskin, Halit; Fidan, Selahaddin Samil (WILEY, 2022)
Alasdair MacIntyre's title, After Virtue: A Study in Moral Theory (AV), is a thought-provoking, influential, ground-breaking title that contributes much to business ethics studies. However, to date, there has not been any systematic and comprehensive study that has examined AV's overall impact on the business ethics landscape. This study thus offers specific and rich information about AV's realized contribution to business ethics over the past 20 years. First, using citation concept analysis (CCA), which refers to a content analysis of statements surrounding in-text citations of AV in articles referring to the primary source, we reveal which AV contents have been either frequently cited or rarely cited. Our findings indicate that although researchers have cited considerably rich and diverse content from AV, there remains a discrepancy for citation contexts when compared to AV's original content related to MacIntyre's multi-level virtue conceptualization. Secondly, using citation depth analysis for how citations of AV spread through a primary source in one of the three categories, for example, limited, intermediate, and comprehensive, we find that AV content has been increasingly cited in both an intermediate and a comprehensive way. We discuss the theoretical and practical implications of this offered study in the management and organization studies.
Keywords: CONTEXT ANALYSIS; INTELLECTUAL STRUCTURE; COCITATION ANALYSIS; DECISION-MAKING; ANALYSIS CCA; MANAGEMENT; GOVERNANCE; KNOWLEDGE; STRATEGY; ORGANIZATIONS; Business & Economics; Social Sciences - Other Topics